UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MANGKOKAN (Polyscias scutellaria. Burm.f) TERHADAP PERTUMBUHAN BAKTERI Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa dan Escherichia coli - Syarifah Roslianizar; Natanael Priltius; Rosina Sitohang; Rahmah (Universitas Sari Mutiara Indonesia, 2021)
Indonesia is a tropical country that has a variety of plants, one of which is the succulent plant (Polyscias scutellaria). Mangkukan plants contain compounds of alkaloids, flavonoids, saponins, tannins, glycosides, steroids, polyphenols, fats. The aim of this study was to determine the antibacterial activity of the ethanolic extract of the Mangkukan leaf (Polyscias scutellaria) against the bacteria Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli. The tests were carried out through the stages of collecting materials, preparing simplicia, making ethanolic extract of kukukan leaves and testing the inhibitory power of basil leaves against Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli bacteria. The manufacture of ethanolic extract of the leaves of the Mangkokan was carried out by the maceration method using 96% ethanol. Antibacterial activity testing was carried out using the agar diffusion method using disc paper. The results of the study based on the results of phytochemical screening showed that the simplicia and ethanol extract of the Mangkokan leaf contained flavonoids, glycosides, saponins, steroids/triterpenes. Meanwhile, in the antibacterial activity test, the ethanol extract of the Mangkokan Leaf had antibacterial or inhibition zones on these bacteria with different concentrations, such as concentrations of 60%, 80% and 100%. Positive control using chloramphenicol and for negative control using sterile distilled water. The ethanol extract of the Mangkukan leaf has antibacterial activity of Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli.